2020
DOI: 10.1186/s13287-020-01752-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells transfected with sFgl2 inhibit the acute rejection of heart transplantation in mice by regulating macrophage activation

Abstract: Background Mesenchymal stem cells (MSCs) have become a promising candidate for cell-based immune therapy for acute rejection (AR) after heart transplantation due to possessing immunomodulatory properties. In this study, we evaluated the efficacy of soluble fibronectin-like protein 2 (sFgl2) overexpressing mesenchymal stem cells (sFgl2-MSCs) in inhibiting AR of heart transplantation in mice by regulating immune tolerance through inducing M2 phenotype macrophage polarization. Methods and results The sFgl2, a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Previous studies indicated that IL-1β derived from macrophages may stimulate MSCs to secrete IL-1RA and PGE2, which leads to the polarization of Ohara et al, 2018;Kojima et al, 2019;Luo et al, 2019;Song et al, 2020 Ischemia/Reperfusion (IR)-induced sterile inflammatory liver injury MSC reprogram macrophage toward anti-inflammatory M2 phenotype Reduced hepatocellular damage; Diminished liver inflammation Li C. et al, 2019;Sheng et al, 2021 Acute liver failure MSC induced anti-inflammatory (M2) macrophages; reduced levels of macrophage Ameliorated hepatocyte death and liver inflammatory response. Li et al, 2017Li et al, , 2021Liu et al, 2018;Hwang et al, 2019;Liang et al, 2019;Shao et al, 2020;Wang et al, 2021 Ben-Mordechai et al, 2013;Xu et al, 2019;Gao et al, 2020;Liao et al, 2020 Atherosclerosis Stimulate the production of anti-inflammatory factor IL-10, and reduce the production of TNF-α by macrophage.…”
Section: Alleviating Autoimmune Diseasesmentioning
confidence: 99%
“…Previous studies indicated that IL-1β derived from macrophages may stimulate MSCs to secrete IL-1RA and PGE2, which leads to the polarization of Ohara et al, 2018;Kojima et al, 2019;Luo et al, 2019;Song et al, 2020 Ischemia/Reperfusion (IR)-induced sterile inflammatory liver injury MSC reprogram macrophage toward anti-inflammatory M2 phenotype Reduced hepatocellular damage; Diminished liver inflammation Li C. et al, 2019;Sheng et al, 2021 Acute liver failure MSC induced anti-inflammatory (M2) macrophages; reduced levels of macrophage Ameliorated hepatocyte death and liver inflammatory response. Li et al, 2017Li et al, , 2021Liu et al, 2018;Hwang et al, 2019;Liang et al, 2019;Shao et al, 2020;Wang et al, 2021 Ben-Mordechai et al, 2013;Xu et al, 2019;Gao et al, 2020;Liao et al, 2020 Atherosclerosis Stimulate the production of anti-inflammatory factor IL-10, and reduce the production of TNF-α by macrophage.…”
Section: Alleviating Autoimmune Diseasesmentioning
confidence: 99%
“…M2 polarization was maintained in the spleen along with elevation of Tregs. In serum, decreased IFN-γ, TNF-α, IL-1β, IL-6, and IL-12 levels and increased IL-4, IL-10, and TGF-β1 levels were observed in sFgl2-AD-MSCs-treated recipients on POD 7 and 14 [ 68 ].…”
Section: Improving Msc Efficacy By Preconditioningmentioning
confidence: 99%
“…Gao et al demonstrated the ability of MSC on macrophage polarization in vivo on a mouse heart transplantation model. 51 They suggested genemodified MSC, such as soluble fibronectin-like protein 2 (sFgl2) overexpressing MSCs, therapy had a better benefit than wild type MSCs. This is of great importance, highlighting the potential of enhancing the MSC derived therapeutic response through further genetic modifications.…”
Section: Mscs Polarize Macrophages To M2 Macrophagesmentioning
confidence: 99%